Compulsory Licensing for Patent Exploitation between Exclusion and Restriction Accordance to the Emirati Law - Al Rawi, Mudhafar (Journal of Legal Sciences, 2023)
The patent means that the inventor is granted a right of intellectual property that is solely acquired by the patent's owner. This study highlights the compulsory licensing provisions that entitle government agencies to exploit the inventor's patent and to exploit it in the manufacture of goods and industries by a third party without the consent of the patent owner for reasons required by the interest of society.This means has been referred to by Decree-Law No. 11 of 2021 on the regulation and protection of industrial property rights. However, the UAE legislator has made recourse to this means an exception, restricting this means by justification required by the public interest of society.The study will focus on the description and justification of compulsory licensing. Then describe the provisions governing compulsory licensing and the philosophy of the UAE legislator by analyzing the legal texts and indicate the effectiveness of the legislator in balancing the interest of society with the interests of inventors.Perhaps one of the most important recommendations reached by the researcher is to call on the UAE legislator to determine how long the licensee can be judged positive for such exploitation and to achieve maximum benefits, especially in the context of satisfying the consumer's needs.